The Concept of Murabahah (Buy and Buy) and Its Applications In The Sharia Financial Services Cooperative Pariri Lema Bariri (KJKS Paleba) - Fauzan Ahmad; Ahdi Topan Sofyan; Eko Suryaningsih (Ridwan Institute, 2022)
Murabahah (buying and selling) is one of the products produced by the concept of Islam in the world of economy. In sharia-based banking, murabahah products are the prima donna that outperforms other products in the financing variant. The development of Islamic banks lately, if we try to analyze the aspects and factors that cause it, one of them is caused by products which in conventional banking are said to be creative products. On the one hand, in the view of the general public, sometimes it becomes a big question, is sharia banking really different from banking with a conventional system. The stigma that arises is that the two systems are basically the same, only the name is different. So this study aims to determine the concept of change (buying and selling) and its application in the world of sharia economics, especially in cooperative institutions. The approach used in this research is a qualitative approach, namely research that intends to understand what is experienced by the research subject, for example behavior, perception, motivation, action, and others holistically. This research was conducted at the Shariah Pariri Lema Bariri Financial Services Cooperative (KJKS PALEBA) in Tepas Village, Brang Rea District, West Sumbawa Regency. Based on the data analysis, it can be concluded that the concept of murabahah is the concept of buying and selling goods in daily transactions that are permitted by religion, one party and the other as a buyer, it's just that its application in the sharia system then becomes multi-transaction due to time and place limitations, the existence of a wakalah function. as a supporting role to bring together sellers (cooperatives) and buyers (members). The price which is the excess in the installments becomes the cooperative's profit as a manifestation of the concept of buying and selling